THE IMAGE OF A HIGHER EDUCATION INSTITUTION, ITS STRUCTURE AND HIERARCHICAL LEVEL: THE CASE OF THE VILNIUS UNIVERSITY FACULTY OF ECONOMICS - Mackelo, Olga; Drūteikienė, Greta (Ekonomika, 2010)
The aim of higher education institutions has been recently broadening, which in turn fostered the competitiveness in attracting students, teachers and financing. Unmistakably, higher education institutions are able to attain these goals only via constant improvement of study quality. Nevertheless, the swelling scale of competition at the country’s and international levels in the higher education sector highlights the image of a higher education institution as another considerable factor.This article presents a specified concept of the image of an organization. This concept is specified while considering the peculiarities of higher education institutions; based on it, the conception of a higher education institution’s image is characterized, its main typologies are distinguished, a structural model and hierarchical levels are presented. The theoretical premises are supported by a student survey of the Faculty of Economics of Vilnius University, one of the most prestigious higher education institutions in Lithuania.